Service Parts Inventory Control with Lateral Transshipment that takes Time - Guangyuan Yang; Rommert Dekker (Tinbergen Institute, 2010)
In equipment-intensive industries such as truck manufacturing, electronics manufacturing, photo copiers,and airliners, service parts are often slow moving items for which, in some cases, the transshipment timeis not negligible. However, this aspect is hardly considered in the existing spare parts literature. We assessthe effect of non-negligible lateral transshipment time on various aspects of spare parts inventory control.Furthermore, we introduce customer-oriented service levels by taking the uncommitted pipeline stocks intoaccount. A case study in the dredging industry shows that lateral transshipment may lead to lower systemperformance, which supports the results from some recent studies. Furthermore, we find that considerablesavings can be obtained when we include the uncommitted pipeline stocks in both base stock allocation andlateral transshipment decisions.
Keywords: C44; 330; Inventory Control; Lateral Transshipment; METRIC; Customer-oriented Service Level; Lagermanagement; Dienstleistungsqualität; Kundenzufriedenheit; Lagerhaltungsmodell